(untitled) (Journal of Universal Science Research, 2023)
Analysis is the basis of diagnosis in medical practice. For these purposes, one important source is digital images. Based on this, we look at the digital image of the blood smear. These data allow us to consider the possibility of diagnosing various diseases. Particular attention in the work is paid to certain methods of digital image analysis. The choice of such methods is based on the analysis task. The article presents examples of digital images of a blood smear and the results of their processing.